FAKTOR_FAKTOR AKTIVITAS KERJA JARAK DEKAT DENGAN KEJADIAN MIOPIA PADA ANAK USIA SEKOLAH - Zakaria Efendi; Nisa Zakiati Umami; Sri Rahayu (Akademi Refraksi Optisi dan Optometry Gapopin, 2021)
Near work activity in school-aged children is one of the risk factors (effects) of myopia. The longer a person focuses his eyesight to look closely, the longer the accommodation. So that over time the eyes will get tired and this condition will trigger blurring in the retina and the eyes become unfocused. Myopia is a form of refractive disorder in which parallel rays coming from an infinite distance by the eye that are not accommodated are refracted at a point in front of the retina, distant vision is blurred, hence myopia is the main cause of visual impairment